Triple bottom line, sustainability and economic development: What binds them together? A bibliometric approach - Lopes, João M. (2023)
The importance given to sustainable development paved the way for the development of the triple bottom line (TBL) concept. TBL is vital for the assessment of nations’ economic development (ED) beyond traditional economic measures. Despite this relevance, few studies still seek to deepen our understanding of the interaction between TLB and ED. Thus, this bibliometric study aimed to analyse the relationship between TBL, sustainability, and ED, adding business strategy concepts such as competitiveness, decision making, planning, and performance. We intended to reinforce the extension of TBL’s dominant rhetoric to sustainable ED. The results revealed the relationship between TBL and ED and allowed the identification of four clusters, from which a theoretical–conceptual model of the theory and application of TBL to achieve ED was formulated. This model can be adopted for the consolidation of ED through the TBL framework and as a tool to support business strategy related to obtaining competitive advantage; decision making; planning; and stimulating economic, social, and environmental performance.